Insight into an unusual lanthanum effect on the oxygen reduction reaction activity of Ruddlesden-Popper-type cation-nonstoichiometric La2−xNiO4+δ (x = 0–0.1) oxides - Chen, Y.; Qian, B.; Yang, G.; Chen, D.; Shao, Zongping (Royal Society of Chemistry, 2015)
The creation of a cation deficiency in the Ln-site of some Ruddlesden-Popper-type Ln2NiO4+δ oxides (Ln = Pr, Nd) can promote the oxygen reduction activity of these materials at elevated temperatures; however, La-nonstoichiometric La2NiO4+δ materials have been reported to behave differently. In this study, a series of La2−xNiO4+δ (x = 0–0.1) materials was synthesized and systematically characterized to obtain information regarding the origin of their different electrochemical behaviors. Based on XRD and HR-TEM characterizations, a high-order La3Ni2O7 phase was detected, even in the case of a slight La deficiency (x = 0.02), and its content increased with the increasing degree of La nonstoichiometry, suggesting the unfavorable formation of a cation deficiency in La2−xNiO4+δ. Such a high-order Ruddlesden-Popper-type oxide typically improves the oxygen reduction activity; however, reduced activity with the increasing La nonstoichiometry of the samples was actually detected based on symmetrical cell tests. In-depth impedance analysis revealed that the deteriorated electrochemical performance was mainly due to the inferior charge transfer process occurring at the electrode/gas interface and/or oxygen ion transfer through the electrolyte/electrode interface. The microstructures of the La-deficient La2−xNiO4+δ electrodes were then carefully observed using SEM. Both the electrode particle interconnection and the adhesion of the electrode layer to the electrolyte were poor, which were related to the poor sintering ability of the high-order La3Ni2O7 phase that deteriorated the electrode performance.